Odpowiedzi

2010-03-06T00:25:09+01:00
A) P = a*h/2 = (2,5pierwiastek z 3 +2,5) * 2,5 /2 = 6,25pierwiastek z 3 + 6,25 / 2 =3,125 pierwiastek z 3 + 3,125
Obw = 5 + 2,5 pierwiastek z 2 + 2,5 pierwiastek z 3 + 2,5=
7,5 + 2,5 pierwiastek z 2 + 2,5 pierwiastek z 3

B) P = (2 pierwiastek z 3 + 2)* 2 pierwiastek z 3 /2 = 20/2 = 10
Obw= 2 + 4pierwiastek z 3 + 2pierwiastek z 3 + 2 pierwiastek z 6 = 2 + 6 pierwiastek z 3 + 2pierwiastek z 6

C) P = ( 3pierwiastek z 6 + 3pierwiastek z 2) *6 /2 = 9 pierwiastek z 6 + 9pierwiastek z 2
Obw = 6 + 3pierwiastek z 2 + 3pierwiastek z 6 + 6 pierwiastek z 2

D) P = (pierwiastek z 3 + 3) * pierwiastek z 3 /2 = 3+ 3pierwiastek z 3 /2 = 1,5 + 1,5 pierwiastek z 3
Obw= pierwiastek z 3 + 3 + pierwiastek z 6 + 2 pierwiastek z 3 = 3pierwiastek z 3 + 3 + pierwiastek z 6
28 3 28